Motivation among university degree students - Jiménez-Manchado, Inmaculada; Sánchez-Bolivar, Lionel (Millenium - Journal of Education, Technologies, and Health, 2025)
Currently, there is growing concern regarding the increasing rates of school dropout across all levels of education. This concern is particularly acute in higher education, as it represents a non-compulsory stage of the educational pathway and, in principle, one chosen voluntarily by students themselves. When analyzing the reasons leading students to drop out, several factors emerge as determinants of attrition; unfortunately, many of these lie beyond the direct influence of university faculty. Among them, the lack of required entry qualifications and limited financial resources to pursue studies at the institution of admission stand out as significant predictors, often resulting in the selection of less desirable or even undesirable courses, which in turn precipitate withdrawal (Itzhaki et al., 2019). Another group of determinants relates to student motivation. The study of motivation has long been a central concern among educators, particularly within higher education. In this context, motivation can be conceptualized as the psychological force that drives individuals to act and sustains them in the pursuit of a goal. The typology proposed by Sánchez-Bolívar and Martínez-Martínez (2022) distinguishes five types of motivation: extrinsic, intrinsic, instrumental, integrative, and transcendent motivation. Extrinsic motivation refers to actions driven by external incentives; that is, the perceived positive outcome of an action determines whether it is undertaken. Conversely, intrinsic motivation arises when the activity itself constitutes the primary source of satisfaction — the individual experiences psychological well-being through engagement in the action, increasing the likelihood of repetition (Sánchez-Bolívar & Martínez-Martínez, 2022). It is essential to recognize that motivation is not a static construct but rather a dynamic continuum, shaped by the interaction of personal, social, and contextual factors (Li, Liu, & Hu, 2023). Contemporary approaches in educational psychology emphasize that the meaning attributed to the task, the sense of competence, and the degree of perceived autonomy are key determinants of motivational quality (Ryan & Deci, 2022; Bottaro & Faria, 2022). Consequently, the role of the university lecturer transcends the mere transmission of knowledge and extends to the creation of learning environments that foster autonomous, enduring, and self-sustaining motivation. According to Ryan and Deci (2022) and their Self-Determination Theory, motivation that begins as extrinsic may, through repeated engagement, evolve into an intrinsic form, thereby enhancing psychological well-being. Between these two poles lies instrumental motivation, characterized by a balance between personal satisfaction and the perceived importance of the outcome (Sánchez-Bolívar & Martínez-Martínez, 2022). These authors argue that true “demotivation” does not exist; rather, they refer to amotivation — a state of motivational alienation in which the individual perceives a disconnection between the performed action and its outcomes. When this perception persists, behavioral engagement ceases (Ryan & Deci, 2022).